(untitled) (Global Journal of Science Frontier Research, 2020)
Cadmium Selenide (CdSe) thin films were deposited by Pulse Laser Deposition(PLD) technique onto Indium Tin Oxide (ITO) coated glass substrates at different substrate temperatures. The structure of CdSe confirmed by using the X-ray diffraction pattern. The surface element analysis and morphology of thin films were done by X-ray photoelectron spectroscopy and Atomic force microscopy, respectively. Raman spectroscopy is used for atomic bond behavior at room temperature and lower than room temperature. The band gap of the thin films was estimated (1.75 eV to 2.3 eV) using the UV-Visible absorption spectra. Electrical behavior (I-V characteristic) of thin films also studied at different temperatures. These films have possible applications in thin films based on solar cells, and sensors.